What Factors Drive Consumer Preference of Dairy Products with Education as Moderator? An Empirical Approach - Rekha, R.; Maruthamuthu, K. (International Review of Management and Marketing, 2024)
The primary goals of this study are to determine the key variables that lead consumers to favour milk products and to assess the degree of consumer knowledge in India. In this study, convenience sampling under the non-probability sampling approach is used to collect data from Indian customers using a structured questionnaire. A multiple-regression model is used to explain consumer choice, and then an analysis of variance (ANOVA) is performed to reveal any significant differences between the factors influencing customer preference for dairy products. An analysis of the variables influencing customers’ purchasing decisions about milk and its products is conducted. The findings indicated that the main variables affecting the decision to purchase milk products are availability, price, quality, and health consciousness. Age, monthly income, and family size were significantly correlated with the amount of milk consumed. This study aids marketing managers in formulating marketing plans that take into account customer preferences, availability, quality, affordability, and health consciousness. The research conclusion addresses consumer likelihood in addition to being beneficial for the entrepreneurial viewpoint. Even if the study presents Indian consumers’ opinions, it restricts the likelihood of the west. Numerous dairy products remain undiscovered due to resource limitations, potentially expanding the area of future study.